PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU - Riski, Desi; Idris, Jamaluddin; Marwan, Marwan (Universitas Islam Negeri Sumatera Utara Medan, 2024)
The aims of this research are (1) to analyze the influence of the principal's transformational leadership style on the performance of high school teachers (2) to analyze the influence of work discipline on the performance of high school teachers (3) to analyze the influence of work motivation on the performance of high school teachers (4) to analyze the influence of the principal's transformational leadership style through work motivation on the performance of high school teachers (5) analyzing the influence of work discipline through work motivation on the performance of high school teachers (6) analyzing the influence of the principal's transformational leadership style, work discipline and work motivation together on the performance of high school teachers. This research uses quantitative methods, an associative approach, a population of 137 teachers, a sample of 102 teachers, a proportional random sampling technique using the Slovin formula at an error level of 5%, a Likert scale questionnaire data collection technique and a path analysis data processing technique. Research findings (1) the principal's transformational leadership style has a direct effect on the performance of high school teachers with a t-count of 3.318, sig 0.001 and beta 0.245 (2) work discipline has a direct effect on the performance of high school teachers with a t-count of 3.962, sig 0.000 and beta 0.294 ( 3) work motivation has a direct effect on the performance of high school teachers with a t value of 6.475, sig 0.000 and beta 0.477 (4) the principal's transformational leadership style has no direct effect through work motivation on the performance of high school teachers amounting to 0.060 (5) work discipline has no direct effect directly through work motivation on the performance of high school teachers amounting to 0.084 (6) the principal's transformational leadership style, work discipline and work motivation jointly influence the performance of high school teachers with an Fcount value of 32.483 and sig 0.000.